Prospects of Implementing Green Economy Policies for Sustainable Development in Bekasi Regency - Heksawan Rahmadi; Sri Susanti Widyasari (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The issue of sustainable development arises along with various environmental impacts due to irresponsible industrial and economic activities, such as river pollution, global warming and emission gaps. Bekasi Regency Regency is a buffer zone for the capital city of Jakarta and is included in the Greater Jakarta area. Initially, Bekasi Regency was a rural and rice-producing area, but with massive development and industrialization, Bekasi Regency experienced a shift in land use. Another situation is the damage to the quality of groundwater, rivers and air due to factory waste. The objective of this research is to describe and analyze the prospect of implementing a green economy in Bekasi Regency so that environmental-based development recommendations can be produced